Sex- and age-specific migratory strategies of blue whales in the northeast Pacific Ocean - Blevins, Christina; Busquets-Vass, Geraldine; Pardo, Mario A.; Gendron, Diane; Jacobsen, Jeff K.; Gómez-Díaz, Francisco; Pérez-Puig, Héctor; Ortega-Ortiz, Christian Daniel; Heckel, Gisela; Urbán R, Jorge; Viloria-Gómora, Lorena; Newsome, Seth D. (Frontiers in Marine Science, 2022)
Migration is a complex behavior that has evolved in multiple taxonomic groups as a means of accessing productive foraging grounds and environmentally stable areas suitable for reproduction. For migratory whales that forage throughout the year because of their high energetic demands, changes in the abundance of prey in different areas along their migratory route(s) can have serious implications for individual fitness and population viability. Thus, identifying the regions these species use to forage and breed while evaluating their migratory plasticity at the individual level can provide key information for their management and conservation. Serial stable isotope analysis of whale baleen, a continuously growing but metabolically inert tissue, has proven useful in generating individual migratory and foraging records over several years prior to death. We measured carbon (δ13C) and nitrogen (δ15N) isotope values along the length of baleen plates collected from thirteen blue whales of different sex and age classes, representing the largest collection analyzed to date in the northeast Pacific Ocean. Adult females exhibited relatively stable seasonal movements between temperate latitude foraging grounds and subtropical breeding grounds, although two skipped migration one year and subsequently moved to the same subtropical breeding ground near the Costa Rica Dome, potentially to give birth. Adult males exhibited two movement strategies with most remaining at temperate latitudes for 3-4 years before death, while two migrated to subtropical breeding grounds. In contrast, movement patterns in juveniles were erratic. These results are potentially driven by the energetic requirements during pregnancy and nursing in adult females, intra-specific competition among adult males, and inexperience in locating prey in juveniles. We also describe baleen δ15N patterns in recently weaned whales (<16.5m) that reflect switching from the consumption of milk to solid food (krill). In addition, baleen δ13C data suggest that weaned whales continue to use stored nutrients (blubber) acquired during the nursing period long after they are weaned. These results broaden our understanding of habitat selection in this species, highlight the importance of nursing for the critical period after weaning, and indicate that the Costa Rica Dome is an important calving region for this endangered population.